2016
DOI: 10.4103/1947-2714.185029
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of efficacy and safety of topical squaric acid dibutylester and diphenylcyclopropenone for the treatment of alopecia areata

Abstract: Background:Topical squaric acid dibutylester and diphenylcyclopropenone are still the most effective therapy for alopecia areata among widely available treatment options. Hence, it is important to know which one is more effective and safer between the two.Aims:The aim of this study was to compare topical squaric acid dibutylester and diphenylcyclopropenone for the treatment of alopecia areata in terms of their efficacy and side effects.Subjects and Methods:In the time period of January–March 2015, a total of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
(19 reference statements)
0
10
0
1
Order By: Relevance
“…Many prognostic factors for DPCP treatment outcome have been described. They include the type of AA, the extent of alopecia, age at disease onset, age at DPCP onset, duration of AA before initiation of DPCP therapy, family history of AA, and presence of atopic dermatitis (Tiwary et al, ). In this study, we found the extent of hair loss before DPCP treatment to be the most prognostic factor for clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many prognostic factors for DPCP treatment outcome have been described. They include the type of AA, the extent of alopecia, age at disease onset, age at DPCP onset, duration of AA before initiation of DPCP therapy, family history of AA, and presence of atopic dermatitis (Tiwary et al, ). In this study, we found the extent of hair loss before DPCP treatment to be the most prognostic factor for clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to an autoimmune basis of AA, several types of treatment modalities have been tried in different studies but none of them have been found to be a definitive and curative treatment (Tiwary et al, 2016), and results until now are not satisfactory for many dermatologists (Wasylyszyn & Borowska, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Se ha propuesto también su uso de forma prolongada, con pautas menos agresivas y menor frecuencia de aplicación, ya que en algunos estudios se ha descrito respuesta mantenida y menor índice de recaídas con esta forma de empleo [33]. El perfil de eficacia y recaídas es similar para las dos opciones de inmunoterapia, aunque Tiwary y colaboradores concluyen que el SABDE es más eficaz y con menos efectos secundarios [34]. De los estudios realizados en formas totales/universales, el de Ohlmeier y colaboradores reporta los mejores resultados, con repoblación superior al 90% en más del 70% de los Dermatology Online Journal || Review pacientes.…”
Section: -Inmunoterapia De Contactounclassified
“…Recent studies showed that warts in children caused by the human papilloma virus could be treated safely by topical application of squaric acid dibutyl ester (SADBE). In addition, SADBE is also successfully used as topical immunomodulator for the treatment of alopecia [5].…”
Section: Introductionmentioning
confidence: 99%